A 6-bit digital CMOS variable gain attenuator with large dynamic range and high linearity-in-dB for ultrasound imaging applications. (January 2019) - Li, Di; Fei, Chunlong; Wu, Xiaopeng; Yang, Yin-Tang
Abstract: A 6-bit digital CMOS variable gain attenuator (VGAT) with 42 dB dynamic range (DR) and high linearity-in-dB was presented. CMOS transistors were used as the shunt devices and attenuation gains with different distribution rules of the shunt transistors ( W / L )s were analyzed and simulated in detail. A geometric series with a length of 42 and a ratio of 1.122 was finally adopted for the ( W / L )s to achieve the 42 dB DR and 1 dB attenuation step size. Fabricated in a 0.18-μm CMOS technology, the proposed VGAT had been integrated in a 4-channel ultrasonic imaging receiver chip and occupied an area of about 0.5 mm × 0.37 mm. The gain errors were limited in the range from −1 dB to −1.3 dB at 27 °C and the DR of the VGAT at different temperatures was retained above 40 dB. The –3 dB bandwidth was about 1.9 GHz at the maximum attenuation and the S11 was better than −11 dB with a 30 MHz input.